A new genus and species of Myzocallidine aphid living on Quercus trojana in Italy (Homoptera Aphididae) (Bollettino di zoologia agraria e bachicoltura, 2024)
Apulicallis trojanae, gen. n., sp. n., (Homoptera Aphididae) is described from ltaly, where it lives on the Macedonian Oak, Quercus trojana Webb. Accounts are given of its morphology (alate viviparous female, fundatrix, alatoid nymph, embryo, male and ovipara), taxonomy, distribution and life cycle.
Keywords: Homoptera Aphididae; Apulicallis trojanae gen. n., sp. n.; Quercus trojana; Italy